The Development of Medical Tourism in Thailand - ภัทรภิญโญพงศ์ วริยา; สุกเพชร เกศรา (Academic and Research Journal of Liberal Arts (Online), 2017)
The Medical tourism industry is a rising star of Thailand’s economy and offers a unique alternative to the issues associated with an excessive reliance on traditional forms of tourism. This article aims to improve the understanding of this tourism market, by clarifying the development of medical tourism in Thailand driven by both public and private sectors. The results of the study reveal three key periods of medical tourism development in Thailand. In the initial period prior to 1997, the medical tourism market relied on a small number of medical tourists seeking specialized surgical procedures. There was no specific government policy encouraging or discouraging medical tourism industries in this period. In the second period between 1997 and 2010 saw the beginning of government policies to encourage medical providers to promote their medical services to medical tourists, in order to compensate for the loss of domestic medical demand caused by the Asian financial crisis. These policies were designed to develop Thailand as an important medical hub in Asia, but they also resulted in the medical tourism industry receiving criticism for negative effects that impacted on health equality in Thailand’s medical services industry. The current period, the period from 2010 onwards has resulted in the Thai government, the Tourism Authority of Thailand and the medical service providers co-operating to support and promote medical tourism in Thailand. Nonetheless, issues such as human resource shortages and the inequality in Thailand’s health care system have not been resolved by involving government agencies.